Supervision of One-Tier Board System in Indonesia : Comparative Study in Malaysia and Singapore - Muhamad Sidik; Suherman Suherman; Atik Winanti (International Journal of Law and Society, 2025)
This study conducts a comprehensive comparative analysis of one-tier board supervision mechanisms across Indonesia, Malaysia, and Singapore, examining the effectiveness of corporate governance frameworks in emerging market contexts. The research employs a doctrinal normative legal methodology, analyzing statutory instruments including Indonesia's Job Creation Law No. 6 of 2023, Malaysia's Companies Act 2016, and Singapore's Companies Act 1967. The introduction of Indonesia's Individual Limited Liability Company (PT Perseorangan) represents a significant paradigmatic shift from traditional two-tier governance structures, necessitating examination of supervisory adequacy within simplified corporate frameworks. The comparative analysis reveals fundamental disparities in regulatory sophistication, with Malaysia and Singapore demonstrating comprehensive fiduciary duty frameworks, mandatory company secretary requirements, and graduated enforcement mechanisms. In contrast, Indonesia's PT Perseorangan exhibits critical institutional deficiencies, including normative conflicts between statutory provisions, limited directorial responsibility regulation, and inadequate enforcement responsiveness. The findings demonstrate that effective one-tier governance systems require sophisticated institutional support mechanisms extending beyond regulatory simplification. Malaysia's stringent Section 213 fiduciary duty provisions and Singapore's technology-enabled enforcement approach provide robust oversight despite absent traditional supervisory boards. The research establishes that successful governance transitions require institutional preparation rather than mere regulatory amendment, with Indonesia's framework requiring substantial reform incorporating company secretary mandates, comprehensive fiduciary duty provisions, and graduated enforcement systems. These findings contribute to institutional theory literature by demonstrating context-dependent governance effectiveness and provide practical recommendations for enhancing corporate accountability in simplified governance structures within emerging market jurisdictions.